Academic Management And Student Promotion In Correlation With Academic Performance - Álvarez-Huertas, Ricardo; González Gil, Marta Elena; Álvarez Posada, José Luis (Migration Letters, 2023)
Standardized tests are widely used to evaluate the quality of teaching and demonstrate student performance. However, there is a lack of theoretically and empirically grounded knowledge on how academic management and student promotion influence academic achievement. In order to contribute to scientific knowledge regarding this identified gap, a quantitative non-experimental, cross-sectional, and correlational study was conducted using stratified sampling. To gather the data, questionnaires were administered to 200 randomly selected teachers from 40 out of 61 public educational institutions in Montería. An instrument was designed and validated, encompassing the variables of academic management (GYP1. G34) and student promotion (GYP2.1290). The results obtained through confirmatory factor analysis demonstrated a significant and positive correlation between these variables (R^2=0.58; F (6,193) = 45.85; p<0.001). The model captures 58% of the variability in the scores obtained in the Saber 11° test of 2021. This finding provides a theoretical-practical reference for continuous institutional improvement and suggests possibilities for future research.